The Path to Sustainable Water Resources Solutions - Peckenham, John; Hart, David; Smith, Sean; Jain, Shaleen; King, Whitney (Maine Policy Review, 2012)
Water is essential both to human survival and to the ecosystems on which people depend. Although Maine is blessed with abundant water sources, managing them is crucial for both short and long-term uses. The authors describe the varying time and spatial scales involved in managing water resources, pointing out that policy decisions made at one time can have far-reaching consequences. They provide illustrations of water-resource projects from Maine’s Sustainability Solutions Initiative, ranging in size from Sebago Laketo vernal pools on individual properties.